Characterizing circumnuclear starbursts in the local universe with the VLA. Issue Volume 15:Issue S359(2020) (March 2019) - Song, Yiqing; Linden, Sean T.; Evans, Aaron S.; Barcos-Muñoz, Loreto; Murphy, Eric J.
Abstract: Nuclear rings are excellent laboratories to study star formation (SF) under extreme conditions. We compiled a sample of 9 galaxies that exhibit bright nuclear rings at 3-33 GHz radio continuum observed with the Jansky Very Large Array, of which 5 are normal star-forming galaxies and 4 are Luminous Infrared Galaxies (LIRGs). Using high frequency radio continuum as an extinction-free tracer of SF, we estimated the size and star formation rate of each nuclear ring and a total of 37 individual circumnuclear star-forming regions. Our results show that majority of the SF in the sample LIRGs take place in their nuclear rings, and circumnuclear SF in local LIRGs are much more spatially concentrated compared to those in the local normal galaxies and previously studied nuclear and extra-nuclear SF in normal galaxies at both low and high redshifts.